Representing ECM composition and EMT pathways in gastric cancer using a new metastatic gene signature - Albano, Francesco; Russi, Sabino; Laurino, Simona; Mazzone, Pellegrino; Di Paola, Giuseppina; Zoppoli, Pietro; Amendola, Elena; Balzamo, Chiara; Bartolo, Ottavia; Ciuffi, Mario; Ignomirelli, Orazio; Sgambato, Alessandro; et al. (Frontiers in Cell and Developmental Biology, 2024)
Introduction Gastric cancer (GC) is an aggressive and heterogeneous malignancy marked by cellular and molecular diversity. In GC, cancer cells invade locally in the stomach at stage I and can progress to metastasis in distant organs by stage IV, where it often becomes fatal. Methods We analyzed gene expression profiles from 719 stage I and stage IV GC patients across seven public datasets, conducting functional enrichment analysis to identify a gene signature linked to disease progression. Additionally, we developed an in vitro model of a simplified extracellular matrix (ECM) for cell-based assays. Results Our analysis identified a progression-associated gene signature (APOD, COL1A2, FSTL1, GEM, LUM, and SPARC) that characterizes stage IV GC. This signature is associated with ECM organization and epithelial-to-mesenchymal transition (EMT), both of which influence the tumor microenvironment by promoting cell invasion and triggering EMT. Discussion This gene signature may help identify stage I GC patients at higher risk, offering potential utility in early-stage patient management. Furthermore, our experimental ECM model may serve as a platform for investigating molecular mechanisms underlying metastatic spread in gastric cancer.